2006
DOI: 10.1577/t04-165.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Solution‐Based versus Laser Ablation Inductively Coupled Plasma Mass Spectrometry for Analysis of Larval Fish Otolith Microelemental Composition

Abstract: Otolith microchemistry has become a widely used tool for fisheries-based research in marine systems. However, its application to systems without well-defined juvenile nursery areas in which distinct otolith elemental signatures can develop (i.e., most freshwater systems) remains limited. In large part, this deficiency is due to unsuitable protocols for reliably processing and analyzing small otoliths of larvae. Herein, we evaluate the abilities of solution-based (SO) and laser ablation (LA) inductively coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(122 citation statements)
references
References 49 publications
3
118
1
Order By: Relevance
“…age 5) is indicative of interannual stability in water chemistry within habitats and demonstrates that differences in otolith Sr:Ca signatures of fish from riverine and high-salinity, floodplain pond habitats (up to 11 mmol/mol) can persist among years. These findings are consistent with previous research that demonstrated strong associations between water and otolith microchemistry (Wells et al 2003) and interannual stability of Sr:Ca signatures in some freshwater environments (Zimmerman and Reeves 2002;Wells et al 2003;Munro et al 2005;Ludsin et al 2006). …”
Section: Utility Of Otolith Dd and Sr:ca Ratio As Environmental Markerssupporting
confidence: 93%
See 3 more Smart Citations
“…age 5) is indicative of interannual stability in water chemistry within habitats and demonstrates that differences in otolith Sr:Ca signatures of fish from riverine and high-salinity, floodplain pond habitats (up to 11 mmol/mol) can persist among years. These findings are consistent with previous research that demonstrated strong associations between water and otolith microchemistry (Wells et al 2003) and interannual stability of Sr:Ca signatures in some freshwater environments (Zimmerman and Reeves 2002;Wells et al 2003;Munro et al 2005;Ludsin et al 2006). …”
Section: Utility Of Otolith Dd and Sr:ca Ratio As Environmental Markerssupporting
confidence: 93%
“…Our findings corroborate those of a few other recent studies that demonstrated that otolith microchemistry and isotopic analysis represent powerful techniques for retrospectively describing the environmental history of fishes that reside solely in freshwaters, including lakes (Joukhadar et al 2002;Brazner et al 2004;Munro et al 2005;Ludsin et al 2006), streams (Wells et al 2003), and small rivers (Bickford and Hannigan 2005). The results of this study demonstrate that otolith elemental and isotopic assays can also be applied to gain valuable insight into fish movement between large rivers and associated lentic floodplain habitats that would be difficult to obtain by other means.…”
Section: Relation Between Fish Age and Source Habitat And Implicationsupporting
confidence: 89%
See 2 more Smart Citations
“…The laser ablated a transect extending from one side of the otolith core to the edge of the opposite side of the otolith along the longest axis of the section (beam diameter = 25 μm, scan rate = 5 μm/s, laser pulse rate = 20 Hz, laser energy level = 75%, wavelength = 266 nm). Otolith core (first 100 µm of the laser transect) Sr:Ca was used to identify natal environment for individual fish; mean otolith radius for age-0 fish ( Isotopic counts were converted to elemental concentrations (μg/g) after correction for gas blank, matrix, and drift effects (Ludsin et al 2006). Strontium concentration was normalized to calcium concentration based on the consideration of calcium as an internal standard and the stoichiometric concentration of calcium in aragonite for each species were evaluated using two-dimensional Kolmogorov-Smirnov (2DKS) tests (Garvey et al 1998).…”
Section: Otolith Stable Isotope and Elemental Analysesmentioning
confidence: 99%